2010
DOI: 10.1152/ajpheart.01236.2009
|View full text |Cite
|
Sign up to set email alerts
|

Properties of WT and mutant hERG K+ channels expressed in neonatal mouse cardiomyocytes

Abstract: Mutations in humanether-a-go-go-related gene 1 (hERG) are linked to long QT syndrome type 2 (LQT2). hERG encodes the pore-forming ␣-subunits that coassemble to form rapidly activating delayed rectifier K ϩ current in the heart. LQT2-linked missense mutations have been extensively studied in noncardiac heterologous expression systems, where biogenic (protein trafficking) and biophysical (gating and permeation) abnormalities have been postulated to underlie the loss-of-function phenotype associated with LQT2 cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…Since the rat neonatal cardiomyocytes may only transiently express the relevant channel, another approach is to use adenoviral or lentiviral vectors containing the cDNA of interest to infect the cells and allow adequate expression for study in a more native system. Comparing the behavior of wild type HERG and KCNQ1 channels with previously characterized deleterious mutants in rat neonatal myocytes has confirmed initial phenotypic characterization (Li et al, 2001;Lin et al, 2010). These groups found that the wild-type and mutant channel behaved generally the same as in cultured cells with some slight differences.…”
Section: Primary Isolated Myocytessupporting
confidence: 59%
“…Since the rat neonatal cardiomyocytes may only transiently express the relevant channel, another approach is to use adenoviral or lentiviral vectors containing the cDNA of interest to infect the cells and allow adequate expression for study in a more native system. Comparing the behavior of wild type HERG and KCNQ1 channels with previously characterized deleterious mutants in rat neonatal myocytes has confirmed initial phenotypic characterization (Li et al, 2001;Lin et al, 2010). These groups found that the wild-type and mutant channel behaved generally the same as in cultured cells with some slight differences.…”
Section: Primary Isolated Myocytessupporting
confidence: 59%
“…Slower inactivation kinetics is not expected to cause a loss of I Kr function, but faster deactivation kinetics have been associated with the LQT2 mutations R56Q and ΔY475 (Berecki et al 2005; Chen et al 1999; Lin et al 2010; Nakajima et al 1999). We tested the impact that accelerating I Kr deactivation kinetics 10-fold has on the ventricular APD90 using the OVVR computational model of a human AP pulsed at 1 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, neonatal mouse cardiomyocytes have been used as a mammalian expression system to study ion channel mutations found in patients with LQTs [28]. In this study, fresh isolated cardiomyocytes from neonatal mouses were transiently transfected with the cDNA encoding the channel of interest using Amaxa Nucleotranfection kit (Lonza Inc.).…”
Section: Approaches That Have Been and Are Currently Used To Study Mumentioning
confidence: 99%